2011
DOI: 10.1007/s11239-011-0601-x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme sensitivity to acenocoumarol therapy in patient with both VKORC.-1639 A/A and CYP2C9*1/*3 genotypes

Abstract: The initiation phase of vitamin K antagonist (VKA) is a challenging and demanding process that can result in adverse event such as bleeding. Dosing is influenced by a variety of acquired factors, while another factor that is associated with the optimal dose is the presence of certain genetic variants. We describe a 73 years old male who required extremely low dose of acenocoumarol (0.33 mg/day) to reach the target INR of 2-2.5. During initiation of VKA he started with usually recommended doses of acenocoumarol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Other studies also demonstrated the influence of age on the dosage of acenocoumarol, but the mechanism of this association has not been fully elucidated yet. [8,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also demonstrated the influence of age on the dosage of acenocoumarol, but the mechanism of this association has not been fully elucidated yet. [8,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Poly morphisms in genes CYP2C9 (encoding the main cytochrome P4590 enzyme) and VKORC1 (encoding the warfarin target vitamin K epoxide reductase) were associated with variability in warfarin dose requirement (45)(46)(47)(48). Current knowledge about the genetic factors affecting other anticoagulants is more limited and this area requires future studies (46).…”
Section: Other Genetic Risk Factorsmentioning
confidence: 99%
“…The hemorrhages are the most common complications in anticoagulation with coumarin derivates (Esmerian et al 2010;Gage and Lesko 2008;Kovac et al 2011;van der Meer et al 1996) and the risk is higher during the first weeks of the therapy (Hylek et al 2007;Li et al 2006). The prolonged episodes of bleeding have been observed in 12% of treated patients (Levine et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Other important factors are age, diet, height, and weight of patients and potential drug interactions, such as co-administration of amiodarone and other medications. The concurrent carriage of CYP2C9*2/*3, VKORC1 1173T/T, and VKORC1-1639 A/A genotypes in patients with higher risk of thrombosis suggests the lowest dose requirement of acenocoumarol and a significantly increased risk of bleeding complications (Kovac et al 2011).…”
Section: Introductionmentioning
confidence: 99%